Cinematic nihilism : encounters, confrontations, overcomings - Marmysz, John, 1964- (Edinburgh University Press, 2017)
Through case studies of popular films, including Prometheus, The Dark Knight Rises, Dawn of the Dead and The Human Centipede, this book re-emphasises the constructive potential of cinematic nihilism.